Persistence in style-adjusted mutual fund returns - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2001)
The literature on mutual fund persistence took a hit with the finding that one-year stock momentum and expense ratios account for most of the persistence in mutual fund performance (Carhart, 1992; Carhart, 1997). However, since equity mutual funds are grouped into styles (e.g., large value, small growth, mid-cap growth, etc.) and are often confined to trading stocks within their style, one should measure fund performance relative to style when investigating managerial ability. Using CRSP mutual fund data and a methodology similar to Carhart (1997), we find that differences in style-adjusted fund returns persist for up to six years. Neither one-year momentum nor expense ratios explain our results. Our results are also robust to controlling for size, book-to-market equity, load, and total net assets. Since manager tenure is about four years, our results suggest that managerial ability may not be as dead as it seems.